Staat, Wirtschaften und Governance - Herbert Strunz (OrdnungsPolitisches Portal (OPO), 2007)
Public well-being is directed to the welfare of all. The state is traditionally the solicitor of this noble good. Its mission is to balance out the different interests of the different social groups. Within this framework, the activities of the different economic actors are of special significance. In times of globalization, economic actors have been enormously dynamised, not always to the benefit of the individual. The much quoted primacy of economy threatens to become far too powerful, influencing all areas of life rather unfavourably. If public well-being is considered a significant social factor, the question of how the different economic agents can contribute to it on an economic level, stands in the foreground. The microeconomic actors can indeed - also because of their different objectives - contribute essentially and in very different ways to public well-being as well as to a prospering economy and society, in spite of all current deficits. There is also a demand for reaction on the political level. More than ever, the state is stipulated to provide ethic bases and to act accordingly in an assortative, long sighted and in the most positive sense of the word regulating way, as well as with social and ecological responsibility.
Keywords: 330; Public well-being; globalization; role of the state